Thwarting galectin-induced immunosuppression in breast cancer - Salatino, Mariana (2013)
Novel therapeutic strategies are needed to counteract breast cancer-associated immunosuppression. Silencing the expression of galectin-1 in a breast carcinoma model inhibited tumor growth and prevented lung metastasis by reducing the frequency and immunosuppressive activity of CD4+CD25+ FOXP3+ regulatory T cells